ESTIMASI PRODUKTIVITAS PADI MENGGUNAKAN TEKNIKPENGINDERAAN JAUH DALAM MENDUKUNG PROGRAM SWASEMBADA PANGAN - Suharini, Erni; Nafi, Ahmad Yazidun; Sanjoto, Tjaturahono Budi (Geo-Image, 2016)
Pati Regency is one of the largest rice-producing areas nationwide. However, data on the productivity of rice plants have been inadequate. So it appears the problem, 1) how the productivity of rice and how to estimate productivity of rice in support of food self-sufficiency program in Pati District? Population rice area Pati regency with Sample 85 points based on the interpretation of NDVI. The sampling method is simple random sampling. The first variable is productivity of paddy and the second variable is rice productivity estimates. The research instrument used questionnaire. Data analysis using the digital image interpretation technique and quantitative descriptive. Comparing the results mean produtivitas rice by BPS with the results of the study (2014) 5.43 with 5.5 tons / ha, the difference of 0.07 tons / ha. Among the data DISPERTANAK with the results of the study (2015) 109480 with 106,188.62 ha / year. There is a difference of 3.00%. So that remote sensing methods utilizing NDVI value in rice plants can be used to estimate the harvest area.